PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERBANKAN DI BURSA EFEK INDONESIA PERODE 2018 - 2020 - Melda Melda; Sumatriani Sumatriani; Ahmadi Usman (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
This study aims to determine Effect of Financial Performance on Firm Value. The Financial Performance measured by using CAR (Capital Adequacy Ratio), NPL (Non Perfoming Loan), NIM (Net Interest margin), BOPO and LDR (Loan to Deposit Ratio). Meanwhile the Firm Value measured by using (PBV) Price to Book Value. This study used secondary data with the sample comprising banking companies listed in the Indonesia Stock Exchange (BEI) in 2018-2020 by using purposive sampling method. There were 25 Commercial Banks that qualified as research samples. Analysis technique used is a classic assumption test covering normality test, mulicolinierity test, heterocedastisity test and autocorrelation test. Other tests are multiple linier regression and hypothesis test using t-statistic and test use f-statistic to test partial regression coefficient in level of significance 5%. The results of this research showed that using CAR (Capital Adequacy Ratio), NPL (Non Perfoming Loan), NIM (Net Interest margin), BOPO and LDR (Loan to Deposit Ratio) has significantly positive effects toward (PBV) Price to Book Value.